Isolation of a Trypanosome Related to Trypanosoma theileri (Kinetoplastea: Trypanosomatidae) from Phlebotomus perfiliewi (Diptera: Psychodidae). (15th July 2018) - Calzolari, Mattia; Rugna, Gianluca; Clementi, Emanuela; Carra, Elena; Pinna, Marco; Bergamini, Federica; Fabbi, Massimo; Dottori, Michele; Sacchi, Luciano; Votýpka, Jan
Abstract : The Trypanosoma theileri group includes several trypanosome species hardly distinguishable due to the lack of discriminating morphological characters. Trypanosomes belonging to this group have been isolated from different bovine, ovine, and cervids in Europe, Africa, Asia, and Americas. The principal vectors of the T. theileri group are considered tabanid flies; however, T. melophagium is transmitted exclusively by sheep keds. In 2016, 128 sand flies out of 2, 728 trapped in Valsamoggia municipality, Italy, were individually dissected and an unknown trypanosome strain, named TrPhp1, was isolated from a female of the sand fly Phlebotomus perfiliewi . Sequence analysis placed this trypanosome in the T. theileri group with very high homology to other trypanosomes detected in European cervids. This is the first report of the T. theileri group isolation from a sand fly, and the possible role of this insect group in the trypanosome transmission cycle is discussed. Within the T. theileri group, the phylogenetic analysis distinguished several lineages, which, unfortunately, do not correspond with their host specificity and their taxonomic status remains ambiguous.